Study of isolated matrix converter for battery management - Wu, Yinghao (2019)
In current society, people’s demand for batteries is increasing year by year, such as electric vehicles and battery energy storage system. This energy storage system can be used to set up microgrids to provide electricity to rural areas where there is no power. Therefore, building a battery energy storage system with high efficiency and high-power density is very important. Electric power is transported from the grid, the alternating current side, to the battery, the direct current side. There are three requirements: galvanic isolation, high frequency, and high-power density. In traditional topology, capacitors are widely used in the converter to reduce the voltage change caused by the power difference between the ac side and the dc side. However, there are some drawbacks. They are very vulnerable in some severe situation, such as high temperature and high humidity so that their lifespans are short. Matrix converter is a perfect substitute for traditional topology. Because their capacity of removing the bulky electrolytic DC-link capacitor, the circuit becomes smaller and lighter, and its lifespan is longer in comparison with the existing technical proposal. In this article, based on space vector modulation, the bidirectional power flow is realized and the current and voltage of the battery can be modulated.